Quality function deployment and Six Sigma : a QFD handbook - Ficalora, Joseph P. (Prentice Hall, 2010)
Make the Most of QFD and the Voice of the Customer in Six Sigma Environments Quality Function Deployment (QFD) techniques have helped thousands of organizations deliver higher-quality, more user-focused product designs. Now, Lou Cohen's classic guide to QFD has been thoroughly updated to fully align QFD with Design for Six Sigma (DFSS) and other state-of-the-art Six Sigma methodologies. Revised by world-class Six Sigma expert Joe Ficalora and his team at Sigma Breakthrough Technologies, this new edition's up-to-date perspective on QFD reflects dozens of successful Six Sigma and DFSS deployments. They offer a start-to-finish methodology for implementing QFD, and systematically illuminate powerful linkages between QFD and Six Sigma, DFSS, Marketing for Six Sigma (MFSS), and Technology for Six Sigma (TFSS). An expanded, start-to-finish case study demonstrates how QFD should function from all angles, from design and marketing to technology and service. Learn how to Identify the roles and advantages of QFD in today's global business environment Understand every element of the House of Quality (HOQ) Use QFD to drive more competitive product and service development Move from the processes you have to the processes you want Anticipate QFD's unique challenges, overcome its obstacles, and deploy it successfully Extend the HOQ concept all the way through project completion Deploy powerful Voice of the Customer (VOC) techniques throughout all phases of development, not just planning Adapt QFD for software development, service development, and organizational planning Whether you're working in operations, engineering, marketing, technology, or service development, this book will help you drive maximum value from all your Six Sigma, QFD, VOC, and DFSS investments.